ANALISIS INITIAL PUBLIC OFFERING (IPO) TERHADAP PROFITABILITAS PERUSAHAAN: STUDI KASUS PADA PT FORE KOPI INDONESIA, TBK - Indah Maha Sari; Risy Riski; Adinda Putri Utami (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the impact of an Initial Public Offering (IPO) on corporate profitability, focusing on PT Fore Kopi Indonesia Tbk. The research employs a descriptive quantitative approach using secondary data obtained from the company's audited annual financial statements for the 2024–2025 period. The analysis was conducted by comparing profitability ratios before and after the IPO, including the Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results indicate that following the IPO, PT Fore Kopi Indonesia Tbk experienced an improvement in profitability performance, as reflected in the increase of GPM from 61.12% to 61.73% and NPM from 5.61% to 6.02%. These improvements demonstrate the company’s enhanced operational efficiency and ability to generate higher profits. However, ROA declined from 9.09% to 7.77%, while ROE decreased from 23.00% to 13.24%. The decline in these ratios was primarily caused by the significant increase in assets and shareholders’ equity resulting from the IPO proceeds, which were allocated to business expansion activities. Consequently, the benefits of these investments have not yet been fully reflected in the returns generated from assets and equity. Overall, the IPO had a positive impact on the company’s revenue growth, net income, and capital structure. The findings suggest that the IPO proceeds were utilized effectively to support business expansion and strengthen the company’s competitive position, although challenges remain in optimizing asset and equity productivity during the post-IPO period.